Pelaksanaan Kegiatan Shalat Zuhur Berjamaah Siswa SD Negeri 07 Kuban Putiah - Febrianti, Mutia; D, Deswalantri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This religious program aims to cultivate religious character, enhance discipline, and foster unity among students. The study describes the implementation of congregational Zuhur prayers within the school environment, identifying supporting and inhibiting factors. Employing a descriptive qualitative research method, the key informants include Islamic Religious Education teachers, with supporting informants comprising the principal, students, and accompanying teachers. Data analysis techniques involve data examination, reduction, and display.The findings indicate that thorough planning, involving effective coordination between the principal, teachers, and students, supported by adequate facilities and infrastructure, enhances the effectiveness of congregational Zuhur prayer activities in schools. The activities commence with the dissemination of schedules and implementation guidelines involving teachers and students. During execution, supervision and guidance by teachers, along with active student participation, are crucial in fostering a familial atmosphere and improving understanding of worship procedures. Consistent implementation of congregational Zuhur prayers has been proven to strengthen religious character and discipline, creating a harmonious and conducive learning environment. Evaluating these activities is a strategic step to measure effectiveness, student involvement, and the impact on character formation and religious values within the educational setting. However, limitations in supporting facilities and students' understanding of prayer procedures may hinder the optimization of these activities.